Simbol, Solidaritas, dan Memori Kolektif: Perspektif Komunikasi Budaya pada Ritual Obor Pattimura di Tuhaha, Maluku Tengah - Souisa, Erland Valerian; Kissya, Vransisca (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This article examines the dynamics of cultural communication within the Obor Pattimura ritual, held in Tuhaha Village, East Saparua District, Central Maluku Regency. The study aims to understand how cultural symbols embedded in the ritual construct social solidarity and collective memory among the local community. Employing a qualitative approach, data were collected through participant observation, in-depth interviews, and content analysis of symbolic elements emerging throughout the ritual procession. The findings reveal that symbols such as the torch, traditional dances, and indigenous songs function not merely as forms of cultural expression, but also as vehicles of symbolic communication that reinforce communal identity and reproduce historical memory of the Maluku people's resistance. Symbolic communication in this ritual plays a vital role in sustaining social cohesion and affirming local values amidst ongoing social change. The novelty of this study lies in its exploration of the interrelation between symbols, collective emotions, and historical memory within the framework of cultural communication—a dimension often overlooked in ritual studies in eastern Indonesia. This article recommends the preservation of such cultural practices as a means to strengthen local identity and advance the development of cultural communication studies within the social sciences and humanities in Indonesia.